Removal of Phenolphthalein from Laboratory Wastewater Using Natural Clay and Activated Carbon - Guemache, Abderezak (Indonesian Journal of Chemistry, 2026)
Dyes from laboratory wastewater are considered a potential source of water contamination. In this study, natural clay and activated carbon were used to remove a colored indicator (phenolphthalein). Both adsorbents were analyzed by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) and the colored indicator was characterized by UV-vis spectrophotometer. The effects of various parameters, such as initial phenolphthalein concentration, contact time, temperature, pH, and decolorization, were studied. Dye removal increased with decreasing initial phenolphthalein concentration and solution contact time. The percentage of phenolphthalein removal increased accordingly, reaching 99% for activated carbon and 98% for natural clay. Langmuir and the Freundlich adsorption models were used to describe the adsorption equilibrium. The data very well fitted with these models. The monolayer adsorption capacities were equal to 31 mg g−1 at pH 8.0 and temperature 27 °C. The adsorption measurements show that the adsorption process is rapid and physical in nature. The results explain that the adsorption process isexothermic and spontaneous physisorption.